Science Fairs as an Annual Students Project - Costa, Manuel F. M. (2008)
In School Education the teacher, the classes, the study’ organization, the school, the social environment… everything is important and will condition the effectiveness of student’s learning process. However if we want our students to learn and care about science, we have to stimulate and offer them the opportunity to put in practice what they are learning or have learned, because for the vast majority of students the better way to “learn is by doing” [1]. Young students had to be stimulated to science and one of the fine ways to do it is by developing scientific projects, like in science fairs, because they offer a better comprehension of science and nature developing skills, fundamental in science but also in the everyday life, and promote a more critical opinion in face of problems [2]. Despite the importance of this kind of activities, in Portugal events like these are still rare, and there is almost no specific literature that could help us in this organization process. There for it was decided to study and organize a science fair in Externato Maria Auxiliadora. The final objective was to promote, in the last week of school’ classes, a science fair were students present their work at the school and community.